2020
DOI: 10.3390/nu13010137
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Child Feeding Practices and Child Growth: A Retrospective Cohort Analysis in Cambodia

Abstract: Appropriate feeding in the first 1000 days of a child’s life is critical for their health and growth. We determined associations between adherence to age-appropriate feeding practices and child growth in Cambodia. Children (n = 1079) were included in the first follow-up (FU) data analyses and followed for 30 months (six FUs). Data were analyzed by generalized linear mixed-effect models. Children who adhered to feeding practices on at least three FUs, with an adequate minimal dietary diversity (MDD), a minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…This is not thought to influence the directionality and size of the effect, as the E-values suggest that unmeasured confounding would have to be large relative to the observed effects. Further, unmeasured confounding would need to be greater than that reported in previous investigations from the same cohort [ 8 , 27 ]. The implications are that this initial descriptive exercise should be followed up by a more intensive research study using long-term cohorts specifically designed to explore the relationship between ECC and growth development.…”
Section: Discussionmentioning
confidence: 99%
“…This is not thought to influence the directionality and size of the effect, as the E-values suggest that unmeasured confounding would have to be large relative to the observed effects. Further, unmeasured confounding would need to be greater than that reported in previous investigations from the same cohort [ 8 , 27 ]. The implications are that this initial descriptive exercise should be followed up by a more intensive research study using long-term cohorts specifically designed to explore the relationship between ECC and growth development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tallying the findings of other scholars [ 33 , 34 ] has also revealed that caregivers’ unsatisfactory feeding practices against the WHO recommendations have been a problem of public concern. The problem is linked significantly with caregivers’ sex, education level, marital status, the total number of children they have, the number of under-five children they have, the place they delivered their babies, their average birth space between children, occupation, and a person who spends much time caring a baby, residency [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a Cambodian specific diet indicator, The Cambodian Complementary Feeding (CCF) variable was calculated based on the Nutrition Handbook for the family, prepared and adapted by the National Cambodian Nutrition Program [36]. It was based on the number of spoons of Chan Chang Koeh and determined according to age and breastfeeding status [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The 2 sets of questionnaires for sociodemographic characteristics and child feeding practices were administered at baseline by trained Cambodian interviewers in Khmer, or translated into the local indigenous language for some minority populations in northeastern provinces. Dietary intake was assessed using a 24-h recall period, based on WHO guidelines and described in published articles on child feeding practices status [28][29][30]. Parents/caregivers were asked to recall and report on breastfeeding frequency, consumed food groups, frequency of meals, and amount of food given during meals using as unit of measure context relevant utensils: spoons and Chan Chang Koeh, a traditional bowl in Southeast Asia.…”
Section: Questionnairesmentioning
confidence: 99%